Explorações Em Onomatopeias E Quadrinhos - Amaral, Thiago De Almeida Castor Do [UNIFESP] (2017)
Being one of the most recognizable and common elements of comics, onomatopoeia have usages and roles much more diverse and rich than what is generally considered. This paper intends to demonstrate the plurality of these resources, still so little identified in studies about the theme. We start out from the hypothesis that there is a discrepancy between what is discussed about the subject and what one can find in the practice. In an attempt to better understand the onomatopoeic phenomenon, we have conducted research in more traditional Linguistics theories, such as Nyrop (1908) and Nogueira (1950), as well as work more closely related to Semantics and Stylistics, cases of Câmara Jr. (1977) and Ullmann (1977), and discussions on the language of comics, such as the ones realized by Cagnin (1975), Cirne (1970) and Ramos (2010), looking for an approximation between them and also for a broader concept of what an onomatopoeia is. We have then contrasted the proposed theories and the practices of usage of onomatopeia in comics, in order to verify up to which point the discussions covered them, by using several examples taken from comics published in the western world, in western languages. These examples were analyzed according to the related theories, especially considering the multimodal nature of comics and the visual-informative characteristics of onomatopoeia in this media. We have verified, then, as initially supposed, that there was a discrepancy between the reach of the theory and the roles given to onomatopoeia in comics. In order to support the discussion of these roles of onomatopeias not yet sufficiently analyzed, we have resorted to works by Marcuschi (2008), Koch (2004), Custódio Filho (2012) and Cavalcante (2011), related to Text Linguistics, especially in relation to the construction of the referential chain and to context and cotext in texts. We have verified that several possibilities of onomatopoeias in comics, little or not discussed, need a closer look. We have identified, then, several constructions of meaning more elaborate than what is generally attributed to onomatopoeias in comics, such as their inferential role, taking an effective part in the narrative chain, definer and defined by elements in the frame, identifier of characters and as a “recognizable staple” of comics, when one considers their aesthetic characteristics.